2003
DOI: 10.1542/peds.111.s1.1202
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Early Hearing Loss Detection in Hawaii

Abstract: Objective. Universal Newborn Hearing Screening began in 2 Honolulu hospitals in 1992, and by 1999, all 14 civilian birthing facilities in Hawaii were providing screening. Examination of 1998 Hawaii data indicated that approximately 13% of infants who did not pass initial hearing screening in the hospital did not return for the indicated follow-up. The purpose of this study was to determine the epidemiologic profile of infants who were born in 1999 and did not return for follow-up. Methods. A pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
0
12
1
Order By: Relevance
“…Younger maternal age was also associated with loss to follow-up in our study, consistent with the findings of Folsom et al (2000), where they found young maternal age as an independent predictor for loss to follow-up for study protocol after failed NHS among NICU and high-risk well-baby nursery patients. These findings contrast with prior studies that did not find maternal age to be a risk factor for completion of the NHS or loss to follow-up after failed NHS among non-NICU babies (Prince et al 2003; Liu et al 2008). Our findings support maternal age as a risk factor for loss to follow-up for the NHS unique to NICU babies.…”
Section: Discussioncontrasting
confidence: 99%
“…Younger maternal age was also associated with loss to follow-up in our study, consistent with the findings of Folsom et al (2000), where they found young maternal age as an independent predictor for loss to follow-up for study protocol after failed NHS among NICU and high-risk well-baby nursery patients. These findings contrast with prior studies that did not find maternal age to be a risk factor for completion of the NHS or loss to follow-up after failed NHS among non-NICU babies (Prince et al 2003; Liu et al 2008). Our findings support maternal age as a risk factor for loss to follow-up for the NHS unique to NICU babies.…”
Section: Discussioncontrasting
confidence: 99%
“…When this factor was incorporated into the logistic regression model, the effect of other programme-level factors decreased. For instance, audiologist involvement reduced the impact of hospital size, which was otherwise shown to be an influential factor in other studies, with larger hospitals having lower LTFU rates compared to smaller hospitals [76,81,82]. Because of the multifaceted barriers that cause LTFU, an audiologist involved in the programme can monitor the performance outcomes of the screening and focus improvement plans within the local context.…”
Section: Discussionmentioning
confidence: 99%
“…Bigger hospitals with more annual births had lower LTFU rates, compared to smaller hospitals [76,81,82]. One study was the exception [68].…”
Section: Loss To Follow-up Rate and Programme Determinantsmentioning
confidence: 93%
“…Christensen et al 30 categorized maternal age as 13 to 24 years and ≥25 years, so in this case, 13 to 24 years were included as young maternal age, and ≥25 years were included as not young. Two studies initially divided maternal smoking status into 3 groups: current smokers, former smokers, and never smokers 21,31,32 . Of the remaining studies, only 2 differentiated smoking during pregnancy, 30,33 while 1 study simply differentiated lifetime smokers and nonsmokers 26 .…”
Section: Methodsmentioning
confidence: 99%
“…21,26 Racial and ethnic categories varied between studies, but most frequently were categorized as white, black, Hispanic, Asian, and other. Less frequently reported groups included American Indian/ Alaskan Native, 26,27,39,41 Native Hawaiian/Pacific Islander, 21,26,39,40 and Filipino. 21 These different classifications and the sometimes separation of race and ethnicity within studies made a comparison of individual racial categories difficult.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%